Conversational Strategies Used by Gilang Widya Permana and Shandy Purnamasari in the SB30 Podcast - Ivana Naomi (Institute of Research and Community Outreach - Petra Christian University, 2022)
This qualitative study was conducted to determine how speakers of different genders employed conversational strategies. In addition, the writer intended to find the similarities and differences in the use of conversational strategies by male and female speakers. Therefore, the writer chose to analyze the guest stars of SB30's podcast that represented both genders. The guest stars were Gilang Widya Permana (male) and Shandy Purnamasari (female). To analyze the data, the writer referred to Gender and Conversational Strategies theory by Coates (2013). Coates (2013) classifies conversational strategies into seven strategies. This study showed that Gilang used six out of seven strategies, while Shandy used all seven. The writer concludes that conversational strategies can be used by men and women, depending on one's emerging condition. Therefore, the chances of using conversational strategies for both genders are equal.